2021
DOI: 10.1007/jhep04(2021)231
|View full text |Cite
|
Sign up to set email alerts
|

Constraining momentum space correlators using slightly broken higher spin symmetry

Abstract: In this work, building up on [1] we present momentum space Ward identities related to broken higher spin symmetry as an alternate approach to computing correlators of spinning operators in interacting theories such as the quasi-fermionic and quasi-bosonic theories. The direct Feynman diagram approach to computing correlation functions is intricate and in general has been performed only in specific kinematic regimes. We use higher spin equations to obtain the parity even and parity odd contributions to two-, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 147 publications
(324 reference statements)
0
22
0
Order By: Relevance
“…The second one, following [11], involved using the technique of spin-raising and weight-shifting operators in momentum space. In [42,43] following the position space analysis in [62,64] it was shown that one could make use of momentum space higher-spin equations arising from Ward identities associated to (weakly broken) higher spin symmetry to compute spinning correlators including the parity-odd ones.…”
Section: Conformal Correlators In Spinor-helicity Variablesmentioning
confidence: 99%
“…The second one, following [11], involved using the technique of spin-raising and weight-shifting operators in momentum space. In [42,43] following the position space analysis in [62,64] it was shown that one could make use of momentum space higher-spin equations arising from Ward identities associated to (weakly broken) higher spin symmetry to compute spinning correlators including the parity-odd ones.…”
Section: Conformal Correlators In Spinor-helicity Variablesmentioning
confidence: 99%
“…To obtain this correlator we consider the action of Q 4 on the four-point function of scalar operators OOOO . Following the steps in the previous sections and making use of the following [62] (a similar identification of the quasi-fermionic correlator has been made in the position and Mellin spaces in [53]) and [55] respectively)…”
Section: T Ooomentioning
confidence: 99%
“…It would also be useful to push the LCT basis to higher values of ∆ max , in order to extract critical exponents and confirm that the critical point is described by the 3d Ising CFT. One useful tool for reaching higher values of ∆ max would be to compute the general expression for CFT three-point functions of spinning operators in momentum space, building on recent results [29,[52][53][54][55][56][57], which would greatly improve the efficiency for computing Hamiltonian matrix elements. Though in practice our Dirichlet basis states do not individually correspond to primary operators, one can construct a map between the two bases, in order to more efficiently construct matrix elements from CFT data.…”
Section: Jhep05(2021)190mentioning
confidence: 99%